Inventory Stability and Resource Allocation under Uncertainty in a Command Economy - Ericson, Richard E. (Econometrica, 1982)
This paper focuses on a theoretical issue involved in modeling the functioning of a centrally planned economy. Results derived in a model of inventory behavior indicate that the uncertain consequences of economic decisions and their cumulative impact on the functioning of the economy need to be explicitly recognized in order to study plan implementation. When this is done the need for institutions or procedures with homeostatic properties, i.e., negative feedback mechanisms, is revealed. Without such mechanisms orders consistent with a feasible plan may be unable to insure implementation of that plan even when all economic agents are perfectly motivated. Three types of feedback mechanisms resolving this difficulty are formulated and discussed with respect to inventory behavior in a centrally planned economy.